Effect of the Chinese New Year Public Holiday on the Glycemic Control of T1DM With Intensive Insulin Therapy - Guo, Keyu; Ye, Jianan; Zhang, Liyin; Tian, Qi; Fan, Li; Ding, Zhiyi; Zhou, Qin; Li, Xia; Zhou, Zhiguang; Yang, Lin (Frontiers in Endocrinology, 2022)
Aims: There is limited evidence that evaluates the glycemic control of type 1 diabetes mellitus (T1DM) dur-ing the Chinese New Year public holiday in China. The Chinese New Year public holiday represents various challenges to glycemic control, especially in T1DM patients, in China. We aimed to assess the effect of the Chinese New Year public holiday on several glucose metrics using flash glucose monitoring (FGM) in patients with T1DM. Methods: Complete FGM data for 1 week before, 1 week during and 1 week after the Chinese New Year public holiday were available for 71 T1DM patients treated with multiple daily insulin injection (MDI) ther-apy (n = 51) or continuous subcutaneous insulin infusion (CSII) treatment (n = 20). The mean age of the study participants was 13 (9, 30) years. Of note, 59.2% of the patients (n = 42) were adults, and 40.8% of the patients (n = 29) were minors. The interval between each two adjacent period was one week. The indicators of mean glucose, glucose variability and time in different glycemic ranges were analyzed. Results: The Chinese New Year public holiday was associated with an increase in mean blood glucose (8.4 ± 1.7 vs. 9.2 ± 2.5; p < 0.001) and time above range (TAR) (27.9% ± 16.6% vs. 35.0% ± 22.3%; p < 0.001) but a decrease in time in range (TIR) (65.1% ± 15.5% vs. 58.0% ± 19.0%; p < 0.001) and coef-ficient of variation (CV) (65.1% ± 15.5% vs. 58.0% ± 19.0%; p < 0.001). There was no significant difference in time below range (TBR). The glycemic control deteriorated during the Chinese New Year public holiday in our study population regardless of age. Interestingly, in the CSII group, none of the metrics of glucose control significantly changed during the Chinese New Year public holiday. Conclusions: These results suggested that less self-management may worsen glycemic control in the short term, indicating a need for more refined management algorithms during the Chinese New Year public holi-day for T1DM patients.